Results of surgical treatment of rectal cancer at the Hospital de Clínicas. Decade 1989-1998. - Canessa, César; Gómez del Valle, María José (Cirugía del Uruguay, 2003)
With the aim to establish the surgical results and application of current technical concepts in rectalcancer surgery, 87 patients with diagnosis of rectal cancer admitted between 1989-1998 were analysed retrospectively. Dukes classification shows the following dist1ibution: : A= 13%; B=22%; C=32%; D=33%. Out of the 69 patients (86%) operated on, 10 cases underwent derivative surgery and 59 excisional procedures, of which 48 were curative intent. Anatomic mesorectal excision were accomplished in 17,6% of resections.